'Nice Korea, Naughty Korea': Media framings of North Korea and the inter-Korean relationship in the London 2012 Olympic Games. (August 2016) - Yoon, Liv; Wilson, Brian
This study examines mainstream news media framings of North Korea and the inter-Korean relationship in the London 2012 Summer Olympic Games, focusing on the role that the media played in privileging particular understandings of nationalism, conflict and reconciliation. Print news articles from South Korea and English-speaking western nations were collected and analyzed. The results illustrate notable differences between South Korean and western media coverage of North Korea's involvement and the inter-Korean relationship. Western representations of North Korea featured discussions of controversies pertaining to the North Korean government, and often deemphasized or dismissed athletes' efforts. South Korean coverage included few reflections on socio-political problems related to North Korea, but highlighted athletic accomplishments. Emphasis on division was also found more often in western coverage of the inter-Korean relationship as compared to South Korean coverage.